Strategy in His image : supporting and sustaining organizational strategy from a Christian perspective - Ricks, Joe M., Jr; Peters, Richard (Professor of management) (Emerald Publishing Limited : IAP - Information Age Publishing, Inc., 2023)
"This book is intended to contribute model bases on a faith-inspired, biblically based perspective that is consistent with the needs of strategic-organizational leadership. We address the spiritual leadership and spirituality at work literature from a Christian perspective. We argue that it is critical for organizations to reconcile workplace spirituality with strategic thinking and business operations because religious identity is still very important in the United Sates, and we present a model to accomplish this reconciliation. While we are not theologians, in presenting our model we do engage in the theological discussion of the relationship between man and God particularly in the context of business. While we review the evolution of the spiritual leadership and spirituality at work literature along with the limited literature that examines these concepts from a Christian perspective, we identify significant obstacles that have thus far kept these concepts on the fringes of general management thinking and practices. After identifying the challenges associated with a Christian approach to the spirituality literature, we offer a model with four principles for Strategic Spirituality based on a Christian perspective of biblical interpretations that also offer the requisite pragmatism for strategic thinking and organizational implementation"--